Characteristics of tuberculosis contact of children with pulmonary tuberculosis - Magdalena Sidhartani; Retno Murti Laila (Indonesian Pediatric Society Publishing House, 2016)
Background Children with tuberculosis (TB) are often asymptomatic, so that if TB is diagnosed in a child, an adult contact should be looked for. We realize the importance of TB control by breaking the chain of transmission, so identification of contact and prompt treatment should be made. Objective To trace contact of children with pulmonary tuberculosis (PTB) and to determine the environmental characteristics associated with TB transmission. Methods Prospective, community based descriptive study was done in 80 children with newly diagnosed PTB treated at Pediatric Pulmonary Ward, Kariadi Hospital, from September 2003 to February 2004. Clinical condition, chest x-ray (CXR), acid fast bacilli (AFB) staining of sputum, and environmental characteristics of adults suspected as TB contact were examined. Data were analyzed by uni- and bivariate analysis using SPSS 11.5. Results Eighty adults with suspected TB were enrolled, 90% were household contacts. There were 63 (79%) confirmed TB contacts in rural and urban area. Fathers were predominates (32%) followed by grandparents (26.3%), relatives (18.7%), and mothers (12.5%). There was no significant difference about internal (household) and external (non-household) family contacts between rural and urban area (P=1.000). In urban area, home transmission is more frequent than rural area (P=0.340). In urban area, the contacts had a better perception but had no better attitude toward treatment, although the difference was not significant. Behavior was worsen in rural area (P=0.214). Poor behavior seldom occurred in those who had enough knowledge of TB, although the difference was not statistically significant (P=0.352). In the urban area, the house of contacts had lower sleeping density (P=0.282), poor ventilation (P=0.306), and higher room temperature (P=0.683). There were no differences in the light intensity and humidity. Conclusion There were 79% confirmed TB contacts in rural and urban area with male predominant. There was no significant difference between household and non-household contacts in rural and urban area. There are different characteristics, such as knowledge, perception, attitude towards treatment, and behavior associated with TB transmission between contacts in the rural and urban area, and between lower, middle, and higher socio- economic level, although the difference is not significant